Characterization of Fracture Toughness of Acrylic Denture Base Materials Using Modified Arcan Specimen Test - Marzroud, A. Pourtaghi; laleh, F.Farhang; Choupani, Naghd Ali (International Journal of Engineering and Technology, 2018)
Acrylic polymers possess diverse applications in the dentistry proteases such as artificial tooth, amendment material of artificial tooth, etc. Nowadays, Poly Methyl Methacrylate (PMMA) is the material which is used in the production of the majority of denture bases. Regarding the clinical process of producing denture bases, the production of microÂ¬cracks would be inevitable. In the present study, through the production of butterfly Arcan specimens and under the loading conditions in different angles, critical loads of specimens and the pure and mixed mode fracture toughness for the acrylic denture base determined. In this study, the fracture toughness and energy release rate have been calculated through computing the geometric-correction coefficients by utilizing ABAQUS finite element software. Furthermore, the numerical studies have been extended to evaluate the effect of elongation of crack length on the fracture toughness and energy release rate at different loading angles.Â Â